2000
DOI: 10.1007/s004310050066
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of childhood inflammatory bowel disease in Wales

Abstract: The overall incidence (95% confidence intervals) for IBD in Wales was 2.6 (1.87-3.48) cases per 100,000 per year. The incidence for Crohn's disease was 1.36 (0.86-2.04) cases per 100,000 per year, for UC 0.75 (0.39-1.28) cases per 100,000 per year and for indeterminate colitis 0.48 (0.2-0.92) cases per 100,000 per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
7
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 9 publications
7
25
7
1
Order By: Relevance
“…The higher proportion of males among the newly diagnosed CD patients is similar to that in previous pediatric [4, 11, 29], but not in adult studies [28, 48, 49]. …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The higher proportion of males among the newly diagnosed CD patients is similar to that in previous pediatric [4, 11, 29], but not in adult studies [28, 48, 49]. …”
Section: Discussionsupporting
confidence: 73%
“…However, it is significantly lower than the retrospective and prospective incidence rates reported in studies in pediatric populations of Western countries [1, 4, 11, 13, 28, 29]. To explore the possibility that it is 16- to 18-year-olds who lower the overall rates by virtue of presenting to the adult specialists, we recalculated the incidence of IBD in 0- to 16-year-olds, similar to many other pediatric studies.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, although many recent reports reveal a male predominance in pediatric CD cases [3,9,10,[22][23][24], our study revealed nearly equal distribution between sexes. No sex preference was observed for UC, which is in keeping with most studies [3,6,10].…”
Section: (British Columbia [Bc]) To 202 (Nova Scotia [Ns])contrasting
confidence: 64%
“…In a recent systematic review of epidemiology, Benchimol et al reported that CD has become more common, with the incidence of UC stable 5. Serial longitudinal studies from Wales showed a sustained rise in new cases of CD and UC between 1983 and 1993, although regional IBD incidence rates stabilised thereafter 2022. In Scotland, the incidence of IBD is also rising and currently stands at 7.82/100 000/year 17.…”
Section: Discussionmentioning
confidence: 99%